FROM JOB TITLES TO SKILL PROFILES: EFFECTS OF SKILLS BASED HIRING ON ORGANIZATIONAL AGILITY AND DIVERSITY - Prabowo, Catur; Harminingtyas, Rudika; Pelupessy, Ig. Henri; Widowati, Maduretno; Fahlefi, Diva Riza (STIE Pelita Nusantara Semarang, 2025)
To examine the causal relationship between Skills Based Hiring (SBH), Organizational Agility (OA), and Workforce Diversity (WD). The study population included all 168 managerial and non-managerial employees, using a census sampling technique. Data were collected through questionnaires, then analyzed using quantitative methods through Partial Least Square (PLS). SBH has a positive and significant effect on OA, which means that skills-based recruitment improves the organization's ability to respond to change, accelerates decision-making, and strengthens cross-functional collaboration and an adaptive learning culture. SBH also has a positive effect on WD, indicating that competency-based selection opens opportunities for individuals from various backgrounds to contribute to the organization. Furthermore, OA is proven to have a positive effect on WD, as well as mediating the relationship between SBH and WD. This means that the implementation of SBH not only has a direct impact on workforce diversity, but also indirectly through increasing organizational agility. The implications of the research emphasize the importance of expanding the application of SBH evenly, strengthening agility through rapid decision-making, cross-functional collaboration, and a culture of continuous learning, as well as developing inclusive training programs across generations and gender to create a work environment that is adaptive, innovative, and responsive to the dynamics of the electricity industry.